Learn better : - Boser, Ulrich (Rodale, 2017)
Learn Better will revolutionize the way students and society alike approach learning and makes the case that being smart is not an innate ability—learning is a skill everyone can master. With Boser as your guide, you will be able to fully capitalize on your brain’s remarkable ability to gain new skills and open up a whole new world of possibilities.